Surgery at a glance - Grace, P. A. [ (Pierce A.)]; Borley, Neil R. (Chichester, UK ; Hoboken, New Jersey : Wiley-Blackwell, 2009)
Following the familiar, easy-to-use at a Glance format, and now in full-colour, Surgery at a Glance is an accessible introduction and revision text for medical students. Fully revised and updated, this at a Glance provides a user-friendly overview of surgery to encapsulate all that the student needs to know.
1. Clinical presentations at a glance -- 2. Surgical diseases at a glance
Includes index
Keywords: Diagnosis, Surgical -- Handbooks, manuals, etc; Operations, Surgical -- Handbooks, manuals, etc; Surgery -- Handbooks, manuals, etc; Diagnosis -- Handbooks; Surgical Procedures, Operative -- handbooks